Determination of Characteristic Constants of Nickel and Manganese Complexes with p-Nitro-o-carboxylazo-chromotropic Acid - Yang, Jia-Xiang; Gao, Hong-Wen; Shi, Shu-Ren; Dong, Hua-Ze; Wang, Ting-Jian; Liu, Qing-Liang (Asian Journal of Chemistry, 2010)
The synthesis of the novel ligand, p-nitro-o-carboxylazo-chromotropic acid (NCBAC) was carried out and it can react with nickel and manganese at pH 9.6. The updated determination of the properties of the complexes was carried out by the spectral correction method instead of ordinary spectrophotometry. The stepwise real absorptivity (ε) and the cumulative stability constant (K) of Ni-NCBAC and Mn-NCBAC complexes was obtained easily. Results showed that the composition ratios of the complexes were Ni : NCBAC = 1 : 1 and Mn : NCBAC = 4 : 1, their cumula- live K 3.57 x 105 and 1.2 x 105 and their ε 1.76 x 104 and 4.49 x 103 L mol-1 cm-1 respectively at 580 nm.